2010
DOI: 10.1038/onc.2010.61
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic sequestration of p53 promotes survival in leukocytes transformed by Theileria

Abstract: The function of the p53 protein as the central effector molecule of the p53 apoptotic pathway was investigated in a reversible model of epigenetic transformation. The infection of bovine leukocytes by the intracellular protozoan parasite Theileria annulata results in parasitedependent transformation and proliferation of the host cells. We found p53 to be largely localized in the host cell cytoplasm and associated with the parasite membrane of isolated schizonts. Curing infected cells of the parasite with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…6A). Other workers have reported that p53 in T. parva-infected cells is associated with the schizont membrane (Haller et al, 2010) In T. parva-infected cells, MDM2 was primarily localized to the host nucleoplasm (Fig. 6B).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…6A). Other workers have reported that p53 in T. parva-infected cells is associated with the schizont membrane (Haller et al, 2010) In T. parva-infected cells, MDM2 was primarily localized to the host nucleoplasm (Fig. 6B).…”
Section: Discussionmentioning
confidence: 58%
“…However, T. parva-infected cells acquire the ability to proliferate indefinitely, avoiding cell-cycle arrest and apoptosis. Indeed, a recent study by Haller et al (2010) demonstrated that p53-mediated host cell apoptosis is suppressed during Theileria infection, but is rapidly re-activated after elimination of the parasite by the anti-parasitic drug treatment (Haller et al, 2010). Notably, we detected an mRNA in T. parva-infected lymphocytes predicted to encoding a protein homologous to mdm2b, which has been reported to have p53-independent tumorigenicity (Steinman et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…T. annulata-transformed leukocytes appear to induce the latter mechanism because TGF-b signaling drives metastasis while altering transcript levels of many TGF-bregulated genes [39], whereas the core signaling components have mostly unaffected expression levels [87]. Theileria parasites are also known to induce the expression of host MYC [34,58], and sequester host p53 in the cytosol [59] to prevent host apoptosis, and these proteins may therefore also play a role in regulating host cell invasiveness.…”
Section: Evasion Of Growth Suppressionmentioning
confidence: 96%
“…Theileria schizonts induce anti-apoptotic proteins such as cellular FLICE-like inhibitory protein (cFLIP) and cellular inhibitor of apoptosis proteins (cIAPs) [25] by activating host IKK complexes [57] and upregulating or maintaining high c-MYC expression [34,58]. Theileria can also inhibit host pro-apoptotic signaling by sequestering host p53 [59] on their cell surface via unknown receptor(s). T. parva infection also confers resistance to Fas/FasLinduced apoptosis [60], which might be crucial for the evasion of cytotoxic T lymphocytes (CTLs) [61] and activation-induced cell death [62].…”
Section: Inhibition Of Cell Death In Theileria-infected Cellsmentioning
confidence: 99%
See 1 more Smart Citation